Miles Morales Shock waves : a Spider-Man graphic novel - Reynolds, Justin A.; Leon, Pablo; Geoffo; Maher, Ariana (2021)
"Miles Morales is a normal kid who happens to juggle school at Brooklyn Visions Academy while swinging through the streets of Brooklyn as Spider-Man. After a disastrous earthquake strikes his mother's birthplace of Puerto Rico, Miles springs into action to help set up a fundraiser for the devastated island. But when a new student's father goes missing, Miles begins to make connections between the disappearance and a giant corporation sponsoring Miles' fundraiser'--Amazon.
GN450L
Decoding demand: 89 (very high) Semantic demand: 100 (very high) Syntactic demand: 71 (high) Structure demand: 87 (very high)
Keywords: Morales, Miles -- (Fictitious character) -- Comic books, strips, etc; Spider-Man -- (Fictitious character) -- Comic books, strips, etc; Superheroes -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Cartoons and comics; Graphic novels; Superhero comics